Hemodynamic and Tubular Changes Induced by Contrast Media. (16th December 2013) - Caiazza, Antonella; Russo, Luigi; Sabbatini, Massimo; Russo, Domenico
Abstract : The incidence of acute kidney injury induced by contrast media (CI-AKI) is the third cause of AKI in hospitalized patients. Contrast media cause relevant alterations both in renal hemodynamics and in renal tubular cell function that lead to CI-AKI. The vasoconstriction of intrarenal vasculature is the main hemodynamic change induced by contrast media; the vasoconstriction is accompanied by a cascade of events leading to ischemia and reduction of glomerular filtration rate. Cytotoxicity of contrast media causes apoptosis of tubular cells with consequent formation of casts and worsening of ischemia. There is an interplay between the negative effects of contrast media on renal hemodynamics and on tubular cell function that leads to activation of renin-angiotensin system and increased production of reactive oxygen species (ROS) within the kidney. Production of ROS intensifies cellular hypoxia through endothelial dysfunction and alteration of mechanisms regulating tubular cells transport. The physiochemical characteristics of contrast media play a critical role in the incidence of CI-AKI. Guidelines suggest the use of either isoosmolar or low-osmolar contrast media rather than high-osmolar contrast media particularly in patients at increased risk of CI-AKI. Older age, presence of atherosclerosis, congestive heart failure, chronic renal disease, nephrotoxic drugs, and diuretics may multiply the risk of CI-AKI.